DAMPAK PENGHINDARAN PAJAK, KEPEMILIKAN BLOCKHOLDER, KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN - Meco Sitardja (Universitas Agung Podomoro, 2017)
The objective (s) of this research wasanalyzing whether tax avoidance, blockholder ownership, independent commissioner, and audit committee have any influence to firm value. This researchusessecondary data andpurposive samplingconsisting of 72 listed companiesin the manufacturing sector in Indonesia. The data was analysed in SPSS using multiple regression. The result shows that tax avoidance, institutional ownership, and independent commissionerdon’t influence significantly on firm value. Then, audit committee has positiveimpact on firm value.Simultaneously, tax avoidance, blockholder ownership, independent commissioner, and audit committee have significant impact on firm value.